Materializing Ritual Practices - Joyce, Rosemary A., 1956-; Johnson, Lisa M. (Lisa Marie) (Book collections on Project MUSE., 2022)
"Ritual action produces sequences of creation, destruction, and transformation, which involve a variety of materials that are active and agential. Explores the deep history of ritual practice in Mexico and Central America and the ways interdisciplinary research can be coordinated to illuminate how rituals create, destroy, and transform social relations"--